Remarques sur les versions paléographique et critique du Cantar de Mio Cid (Studia Iberystyczne, 2011)
Notes on Paleographic and Critical Versions of the Cantar de Mio CidAccording to Yakov Malkiel, Old Spanish forms vide < Latin vīdī and vido < vīdit are to be accounted for by what he calls “paradigmatic resistance to sound change”. The present writer believes that such a phenomenon does not exist, he examined all forms of the verb ver < vidēre in Cantar de Mio Cid and arrived at the conclusion that in the original version of the poem there were no forms with intervocalic -d-, while the forms vide, vido were arbitrarily introduced by Menéndez Pidal. The article also deals with the possessive pronouns mi/mio, su/so and forms like cuemo/quomo.